Margarida and dourado: new avocado cultivars. Some physical and chemical fruit characteristics - Carvalho, Sérgio Luiz Colucci de; Vieira, Carmem Silvia; Neves, Pedro Manoel Oliveira Janeiro (Pesquisa Agropecuaria Brasileira, 2014)
Physical and chemical characteristics of fruit of two new avocado cultivars were studied. The cultivars showed promising characteristics of cold tolerance and off season maturity under North Parana conditions. 'Margarida' produces very largo fruits with high percentage of flesh and medium oil content. Dourado produces large fruits with medium percentage of flesh, dark-yellow flesh and medium oil content.